Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos, Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg K.N. (Advanced Materials Interfaces)
Keywords: General Medicine

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine

C 1 N 1 Thin Films from Guanine Decomposition Fragments - Jerigová, Mária; Heske, Julian; Kühne, ThomasD.; Tian, Zhihong; Tovar, Michael; Odziomek, Mateusz; Lopez Salas, Nieves (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

The Structure of Water in Silica Mesopores – Influence of the Pore Wall Polarity - Weinberger, Christian; Zysk, Frederik; Hartmann, Marc; Kaliannan, Naveen; Keil, Waldemar; Kühne, Thomas; Tiemann, Michael (Advanced Materials Interfaces)
In the spatial confinement of cylindrical mesopores with diameters of a few nanometers, water molecules experience restrictions in hydrogen bonding. This leads to a different behavior regarding the molecular orientational freedom (‘structure of water') compared to the bulk liquid state. In addition to the pore size, the behavior is also strongly affected by the strength of the pore wall-to-water interactions, that is, the pore wall polarity. In this work, this is studied both experimentally and theoretically. The surface polarity of mesoporous silica (SiO2) is modified by functionalization with trimethylsilyl moieties, resulting in a change from a hydrophilic (pristine) to a hydrophobic pore wall. The mesopore surface is characterized by N2 and H2O sorption experiments. Those results are combined with IR spectroscopy to investigate pore wall-to-water interactions leading to different structures of water in the mesopore. Furthermore, the water's structure is studied theoretically to gain deeper insight into the interfacial interactions. For this purpose, the structure of water is analyzed by pairing densities, coordination, and angular distributions with a novel adaptation of surface-specific sum-frequency generation calculation for pore environments.
Keywords: Mechanical Engineering; Mechanics of Materials

Mechanism and Kinetics of the Thermal Decomposition of Fe(C5H5)2 in Inert and Reductive Atmosphere: A Synchrotron‐Assisted Investigation in A Microreactor - Grimm, Sebastian; Hemberger, Patrick; Kasper, Tina; Atakan, Burak (Advanced Materials Interfaces)
Abstract The decomposition and reduction of ferrocene, an important precursor for iron chemical vapor deposition and catalyst for nanotube synthesis, is investigated in the gas‐phase. Reactive intermediates are detected to understand the underlying chemistry by using a microreactor coupled to a synchrotron light source. Utilizing soft photoionization coupled with photoelectron‐photoion coincidence detection enables us to characterize exclusive intermediates isomer‐selectively. A reaction mechanism for the ferrocene decomposition is proposed, which proceeds as a two‐step process. Initially, the molecule decomposes in a homogeneous surface reaction at temperatures <900 K, leading to products such as cyclopentadiene and cyclopentadienyl radicals that are immediately released to the gas‐phase. At higher temperatures, ferrocene rapidly decomposes in the gas‐phase, losing two cyclopentadienyl radicals in conjunction with iron. The addition of hydrogen to the reaction mixture reduces the decomposition temperature, and changes the branching ratio of the products. This change is mainly attributed to the H‐addition of cyclopentadienyl radicals on the surface, which leads to a release of cyclopentadiene into the gas‐phase. On the surface, ligand fragments may also undergo a series of catalytic H‐losses leading most probably to a high carbon content in the film. Finally, Arrhenius parameters for both global reactions are presented.
Keywords: Mechanical Engineering; Mechanics of Materials

Stimulation and Enhancement of Near‐Band‐Edge Emission in Zinc Oxide by Distributed Bragg Reflectors - Kothe, Linda; Albert, Maximilian; Meier, Cedrik; Wagner, Thorsten; Tiemann, Michael (Advanced Materials Interfaces)
The free exciton transition (near-band-edge emission, NBE) of ZnO at ≈388 nm can be strongly enhanced and even stimulated by an underlying photonic structure. 1D Photonic crystals, so-called distributed Bragg reflectors, are utilized to suppress the deep-level emission of ZnO (DLE, ≈500–530 nm). The reflector stacks are fabricated in a layer-by-layer procedure by wet-chemical synthesis. They consist of low-ε porous SiO2 layers and high-ε TiO2 layers. Varying the thickness of the SiO2 layers allows tuning the optical bandgap in a wide range between ≈420 and 800 nm. A ZnO layer is deposited on top of the reflector stacks by sol–gel synthesis. The spontaneous photoluminescence (PL) emission of the ZnO film is modulated by the photonic structure. When the optical bandgap of the reflector is in resonance with the deep-level emission of ZnO (DLE, ≈500–530 nm), then this defect-related emission mode is suppressed. Strong NBE emission is observed even when the ZnO layer does not show any NBE emission (due to low crystallinity) in the absence of the photonic structure. With this cost-efficient synthesis method, emitters for, e.g., luminescent gas sensors can be fabricated.
Keywords: Mechanical Engineering; Mechanics of Materials

Selective Modification of Hierarchical Pores and Surfaces in Nanoporous Materials - Tiemann, Michael; Weinberger, Christian (Advanced Materials Interfaces)
Tailor-made ordered mesoporous materials bear great potential in numerous fields of application where large interfaces are required. However, the inherent surfacechemical properties of conventional materials, such as silica, carbon or organosilica, poses some limitations with respect to their application. Surface manipulation by functionalization with chemically more reactive groups is one way to improve materials for their desired purpose. Another approach is the design of high surface-area composite materials. The surface manipulation, either by functionalization or by introducing guest species, can be performed selectively. This means that when several distinct, i.e. , hierarchical, types of surfaces or pore systems exist in a material, each of them may be chosen for manipulation. Several strategies can be identified to achieve this goal. Molecules or molecule assemblies can be utilized to temporarily protect pores or surfaces (soft protection), while manipulation occurs at the accessible sites. This approach is a recurring motive in this review and can also be applied to rigid template matrices (hard protection). Furthermore, the size of functionalization agents (size protection) and their reactivity/diffusion (kinetic protection) into the pores can also be utilized to achieve selectivity. In addition, challenges in the synthesis and characterization of selectively manipulated ordered mesoporous materials are discussed.

Validation of a Terminally Amino Functionalized Tetra‐Alkyl Sn(IV) Precursor in Metal–Organic Chemical Vapor Deposition of SnO 2 Thin Films: Study of Film Growth Characteristics, Optical, and Electrical Properties - Zanders, David; Ciftyurek, Engin; Hoppe, Christian; de los Arcos de Pedro, Maria Teresa; Kostka, Aleksander; Rogalla, Detlef; Grundmeier, Guido; Schierbaum, Klaus Dieter; Devi, Anjana (Advanced Materials Interfaces)